Modelos de innovación para la mejor organización del departamento de recursos humanos en el área administrativa en empresas pymes - Infante Quiroz, María Del Carmen (2010)
This work aims to strengthen the human resources department in the administrative area through the integration of technology, communication, training, organization, and so may reward better service to both company and customers and in turn achieve objectives of both the department and the company in general. An organization is a pattern of relationships through which people, under the command of Managers pursue common goals. These goals are a product of the decision making process called Planning. The goals that managers develop because of planning tend to be ambitious, long-range and without fixed end. In turn, the goal is to develop innovations in the human resources department, for which there are no such problems that often has led some companies to close not only for lack of money, but sometimes the little training that employees have on the operation of the company. This is where research on obtaining new innovations in this field, as indicated above is the one who moves the company. The value given to the research is that employees feel comfortable and satisfied in their work area, and so there is great attention to the customer who is the second part of great importance within an organization.